2009
DOI: 10.1097/sap.0b013e318195361e
|View full text |Cite
|
Sign up to set email alerts
|

Double Pedicled Perforator Flap to Close Flank Defects

Abstract: Large defects following resection of skin cancers are sometimes a challenge for the reconstructive surgeon. Although skin grafts are considered as the first choice for reconstruction of large skin defects at the trunk region, pedicled or free flaps provide sometimes a superior functional and aesthetic outcome. Perforator flaps represent a valuable option for these patients. The progress in understanding the perforator vessel system of the body facilitated the development of a plethora of novel pedicled flaps w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The average level of evidence was 4.29, with 4 level 3 studies, 32 level 4 studies, and 20 level 5 studies. Multiple options for reconstruction were described including free style perforator flap, 39 lumbar artery perforator (LAP) flap, 6,8,1012 paraspinous muscle flap, 2,1317 SGAP, 10,14,1822 inferior gluteal artery perforator, 19 intercostal artery perforator flap, 8,10,11,20,23,24 gluteus maximus musculocutaneous flap, 1,2,13,2529 reverse latissimus dorsi flap, 2,7,13,27,3035 lateral intercostal artery perforator–based latissimus dorsi flap, 36 external oblique musculocutaneous pedicled flap, 37 pedicled omental flap, 3840 free flap, 7,13,14,4155 and total leg flap. 56 The most frequently described method of lumbar wound reconstruction was free flap with 18 articles, followed by reverse latissimus dorsi flap reconstruction with 10 articles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The average level of evidence was 4.29, with 4 level 3 studies, 32 level 4 studies, and 20 level 5 studies. Multiple options for reconstruction were described including free style perforator flap, 39 lumbar artery perforator (LAP) flap, 6,8,1012 paraspinous muscle flap, 2,1317 SGAP, 10,14,1822 inferior gluteal artery perforator, 19 intercostal artery perforator flap, 8,10,11,20,23,24 gluteus maximus musculocutaneous flap, 1,2,13,2529 reverse latissimus dorsi flap, 2,7,13,27,3035 lateral intercostal artery perforator–based latissimus dorsi flap, 36 external oblique musculocutaneous pedicled flap, 37 pedicled omental flap, 3840 free flap, 7,13,14,4155 and total leg flap. 56 The most frequently described method of lumbar wound reconstruction was free flap with 18 articles, followed by reverse latissimus dorsi flap reconstruction with 10 articles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In their cases, the type A chain-like variant was used to cover defects involving 2 different units of the hand, and the type B “kiss” pattern was required to resurface a large, single unit defect of the hand. Some other reports, such as “double-helix flap to close a massive circular soft-tissue defect,” [25] “multiple V-Y advancement and rotation flaps for a large cheek defect” [26] and “double pedicled perforator flap to close flank defects” [27] embody obvious elements of partition concept. What is more, some literature [28] had reported reconstruction of large defects with multiple pedicled flaps, but only case report, in which skin grafting also be used.…”
Section: Discussionmentioning
confidence: 99%
“…Review of literature shows a number of studies reconstructing large defect. [26] The various options available are skin grafting, artificial dermis, pedicled myocutaneous flaps, and free flaps. To date, a single all-round method has yet to emerge to deal with all sorts of wounds.…”
Section: Introductionmentioning
confidence: 99%
“…52 D' Arpa et al noted that the longer length of perforators over the trunk permits a greater range of movement, allowing an extensive arc of rotation with little concern about the torsion of the perforator and the blood supply. Studies have demonstrated that large flaps with an orientation perpendicular to the longitudinal axis of the cutaneous dermatomes can be successfully transferred to the trunk 53 ( Fig. 5 ).…”
Section: Applicationsmentioning
confidence: 99%